ANALYSIS OF WATER BALANCE ON SOYBEAN CULTIVATION (Glycine max [L] Merr.) IN DRY LAND - -, Oktaviani; Triyono, Sugeng; Haryono, Nugroho (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
ABSTRACTSoybean is one important food crop in Indonesia after rice and corn. In 2008 to 2010, the amount of soybean harvest has fluctuated. One effort to increase the soybean yield is by using the expansion programs to exploit dry lands. However, water scarcity is the main problem faced in dry land cultivation.  For this reason, study on optimalization of water use become very important and potential of water harvesting is needed to be explored.  This study aimed to analyze and to partition the water balance at soybean cultivation, and also to explore the potential of rainwater harvesting.  The experiment was conducted at the Integrated Field Laboratory of the College of Agriculture, University of Lampung from 15 October 2011 to 6 January 2012.  The observations were carried out by constructing 8 plots, 2x1 m2 each, and in a longitudinal direction of the 5-6% slope.  Four of the experimental plots were sealed with plastic liner and another four pots were left without liner.  Each plot was equipped with a 1x0,5x0,5 m3 water storage pond at the down end of the plot.  Physical properties were determined at the beginning experiment; while rainfall, soil moisture, and water surface of the ponds were monitored evey day.  Soybean yield was weighed at the harvest time. The results showed that water balance could be divided into input and output.  Water input was partitioned into rainfall 41,56% and irrigation 58,44%.  Water output was partitioned into runoff 6,76%, percolation 13,74%, evapotranspiration 74,35%, moisture stored in the soil 0,20%, and irrigation surcharge 5,04%.  Irrigation efficiency was found about 91%, while rainwater harvested contributed 20,74% of the irrigation total.  Potential of productivity was found to be 3,3 ton soybean yield per ha, and potential water use productivity was about 0,74 kg soybean per m3 irrigation water. Keywords: evapotranspiration, soybean, surface runoff, water balance, water harvesting.